(untitled) - McShane, Ian; 1942-; Cheng, Long; 1954-; Rogen, Seth; 1982-; Liu, Lucy; 1968-; 1964-; Cross, David; Kim, Randall Duk.; Hong, James; et al. (DreamWorks Animation, 2008)
Irreverent slacker panda Po is the biggest fan of Kung Fu around ... which doesnt exactly come in handy working every day in his familys noodle shop. Unexpectedly chosen to fulfill an ancient prophecy, Pos dreams become reality when he joins the world of Kung Fu and studies alongside his idols, the legendary Furious Five--Tigress, Crane, Mantis, Viper and Monkey--under the leadership of their guru, Master Shifu. Before they know it, the vengeful and treacherous snow leopard Tai Lung is headed their way, and its up to Po to defend everyone from the oncoming threat. Can he turn his dreams of becoming a Kung Fu master into reality? Po puts his heart - and his girth - into the task, and the unlikely hero ultimately finds that his greatest weaknesses turn out to be his greatest strengths.
Keywords: Drama; Friendship; Drama; China; Weapons, Ancient; Drama; Revenge; Drama; Quests (Expeditions); Drama; Training; Kung fu; Drama; Pandas; China; Drama; Video recordings for the hearing impaired; Animated films; Comedy films; Martial arts films